Global lessons for strengthening breastfeeding as a key pillar of food security - Tomori, Cecília (Frontiers in Public Health, 2023)
Breastfeeding is identified as a central pillar of food security by the World Health Organization, however globally significant challenges remain in achieving breastfeeding targets for early initiation, exclusive breastfeeding for 6 months, and continued breastfeeding for 2 years and beyond. Inadequate support in health systems, poor maternity protections and workplace policies, and insufficient regulation of commercial milk formulas, among other barriers, continue to undermine this key pillar across nations. This paper highlights the central importance of breastfeeding for food security across diverse global settings by examining three case studies: Honduras, Pakistan and the USA. The cases highlight the complex layering and intersections of key challenges that threaten breastfeeding in the era of pandemics, the climate crisis, conflict and global inequality. Lessons drawn from these case studies, combined with additional insights, reinforce the importance of multisectorial collaboration to scale up investment in creating equitable, enabling environments for breastfeeding. These structural and systems approaches can successfully strengthen the breastfeeding ecosystem to ensure greater first food system resilience in the face of global crises, which compound maternal and infant vulnerabilities. Additionally, the cases add urgency for greater attention to prioritizing breastfeeding and incorporating IYCF-E protocols into disaster preparedness and management into the policy agenda, as well as ensuring that first food security is considered in energy policy. An integrated approach to policy change is necessary to recognize and strengthen breastfeeding as a pivotal part of ensuring food security across the globe.